Persistent T cell-mediated immune responses against Omicron variants after the third COVID-19 mRNA vaccine dose - Belik, Milja; Liedes, Oona; Vara, Saimi; Haveri, Anu; Pöysti, Sakari; Kolehmainen, Pekka; Maljanen, Sari; Huttunen, Moona; Reinholm, Arttu; Lundberg, Rickard; Skön, Marika; Österlund, Pamela; et al. (Frontiers in Immunology, 2023)
Abstract The prime-boost COVID-19 mRNA vaccination strategy has proven to be effective against severe COVID-19 disease and death. However, concerns have been raised due to decreasing neutralizing antibody levels after COVID-19 vaccination and due to the emergence of new immuno-evasive SARS-CoV-2 variants that may require additional booster vaccinations. Here we show that within the vaccinated health care workers (HCWs), the third mRNA vaccine dose recalls both humoral and T cell-mediated immune responses and induces high levels of neutralizing antibodies against Omicron BA.1 and BA.2 variants. Three weeks after the third vaccine dose, SARS-CoV-2 wild type spike protein-specific CD4+ and CD8+ T cells are observed in 82% and 71% of HCWs, respectively, and the T cells cross-recognize both Omicron BA.1 and BA.2 spike peptides. Although the levels of neutralizing antibodies against Omicron BA.1 and BA.2 decline 2.5 to 3.8-fold three months after the third dose, memory CD4+ T cell responses are maintained for at least eight months post the second dose and three months post the third vaccine dose suggesting durable immune protection.